Murky waters: Searching for structure in genetically depauperate blue threadfin populations of Western Australia - Horne, J.; Momigliano, P.; Van Herwerden, L.; Newman, Stephen (Elsevier BV, 2013)
The blue threadfin (Eleutheronema tetradactylum) is an exploited fishery species in southeast Asia andAustralia. Demographic studies have revealed fine-scale stock structure throughout the Australian coastline, with demographically isolated populations separated by only tens of km. Similarly, populationgenetic analysis revealed fine-scale structure across most of its Australian range with important implications for fisheries management. However, in northern Western Australia, genetic stock structureanalysis showed a contradictory lack of structure. In the present study, one mtDNA marker and a suiteof five microsatellite loci were used to further investigate the stock structure of Western Australian bluethreadfin populations. By increasing sample sizes from previously investigated areas: Roebuck Bay (n = 93 adults) and Eighty-mile Beach (n = 92 adults and 163 recruits from two settlement cohorts), we were able to detect subtle genetic differentiation that was previously obscured by low levels of genetic polymorphism. Therefore, the same fine-scale stock structure that has been observed elsewhere in this species also appears to exist in Western Australia. This has clear ramifications for a revised management strategy that incorporates the fine scale structuring of northwest Western Australian stocks of the blue threadfin.